(untitled) (Brazilian Journal of Radiation Sciences, 2023)
A planar nuclear medicine image can be used to estimate dosimetry during iodine therapy. To this end, radionuclide activity distribution should be quantified in the patient’s body in terms of a calibration coefficient. This coefficient allows the net counts to correlate with the image’s activity. This study aims propose a simple and easy calibration protocol to quantify 131I activity in thyroid phantom by molecular planar images. Were acquired 13 planar images of different phantoms: thyroid phantom of symmetrical lobes; thyroid phantom of asymmetrical lobes; the Jacszack cylinder phantom with a syringe surrounded by air and water, and finally a plastic bottle containing a syringe with radionuclide. We applied the 131I radionuclide in a General Electric gamma camera, model Discovery NM/CT 670 with a high energy general purpose parallel hole collimator above the phantoms positioned at camera bed. The calibration coefficient of the gamma camera and the standard deviation were determined for each phantom; the average calibration coefficient obtained was 0.062±0.006 MBq/cps. The results suggested that the phantoms applied as too the calibration coefficient obtained by them can provides reasonable value for the gamma camera calibration factor for iodine 131, therefore an accurate evaluation of the scattering media as the source detector distance could impose higher variability and uncertainties on results.